2007
DOI: 10.1029/2006jd007541
|View full text |Cite
|
Sign up to set email alerts
|

Subregional precipitation climate of the Caribbean and relationships with ENSO and NAO

Abstract: [1] Thirty-five meteorological stations encompassing the Caribbean region (Cuba, Bahamas, Jamaica, Dominican Republic, Puerto Rico, US Virgin Islands, St. Maarten, and Barbados) were analyzed over the time interval 1951-1981 to assess regional precipitation patterns and their relationships with the North Atlantic Oscillation (NAO) and El Niño-Southern Oscillation (ENSO). Application of factor analysis to these series revealed the existence of four geographically distinct precipitation regions, (C1) western Cub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
161
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(172 citation statements)
references
References 36 publications
(68 reference statements)
9
161
2
Order By: Relevance
“…As compared to previous droughts that also occurred during strong El Niño events (e.g., in 1997–1998), the Pan‐Caribbean drought was considerably more severe (Herrera & Ault, 2017), and it affected regions usually associated with wet conditions during El Niño, such as western Cuba (Jury et al, 2007). …”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…As compared to previous droughts that also occurred during strong El Niño events (e.g., in 1997–1998), the Pan‐Caribbean drought was considerably more severe (Herrera & Ault, 2017), and it affected regions usually associated with wet conditions during El Niño, such as western Cuba (Jury et al, 2007). …”
Section: Introductionmentioning
confidence: 79%
“…Because of the relatively coarse horizontal resolution of state‐of‐the‐art gridded observationally based climate products, which varies from 0.5° to 2.5° (~55 to ~280 km, respectively) and thus fails to resolve many of the Lesser Antilles (Dai, 2011; Jury et al, 2007; van der Schrier et al, 2013), we used statistically downscaled observed monthly precipitation and temperature ( T min , T mean , and T max ) data from the Global Precipitation Climatology Centre (Schneider, Becker, Finger, Meyer‐Christoffer, Rudolf, et al, 2015; Schneider, Becker, Finger, Meyer‐Christoffer, & Ziese, 2015) and Berkeley Earth Surface Temperature (Rohde et al, 2013), respectively. The validation of downscaled products and further details of the downscaling and bias‐correction procedures are described in Supporting Information S1 and in Herrera and Ault (2017).…”
Section: Methodsmentioning
confidence: 99%
“…The target data include station rainfall averaged into four Caribbean Antilles Island areas, based on the cluster analysis of Jury et al (2007): (1) western Cuba (annual mean and standard deviation: 103, 53 mm/month), (2) eastern Cuba (82, 40), (3) Dominican Republic and Puerto Rico (92,42), and (4) the Lesser Antilles of the east Caribbean (92,45). The station data were extracted from NCDC/GHCN, and gaps were filled using gridded rainfall estimates from NCEP, based on the CMAP reconstruction technique (Xie and Arkin, 1997;Chen et al, 2002;Yin et al, 2004), available at the website http://iridl.ldeo.columbia.edu/SOURCES/.NOAA/.…”
Section: Methodsmentioning
confidence: 99%
“…The station data were extracted from NCDC/GHCN, and gaps were filled using gridded rainfall estimates from NCEP, based on the CMAP reconstruction technique (Xie and Arkin, 1997;Chen et al, 2002;Yin et al, 2004), available at the website http://iridl.ldeo.columbia.edu/SOURCES/.NOAA/. In the study by Jury et al (2007), rainfall data were truncated at 1981, but here, we employ a record extending from 1951 to 2005. The rainfall data are divided into early Figure 1 illustrates the percentage of variance explained by the leading principal components for the seasonal (SEAS) and anomaly (ANOM) time-series.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation